Penatalaksanaan celah bibir - Putri Sekar Palupi, Anggraeny (Jurnal Kedokteran Gigi Terpadu, 2024)
Cleft-lip is one of the congenital abnormalities that often occur in the orofacial area. Patients with orofacial cleft abnormalities need to be treated in the right way and at the right time in order to get functional and aesthetic results. Cleft lip management involves interdisciplinary collaboration from dentists, oral surgeons, orthodontists, prosthodontists, ear, nose, throat, speech specialists, and others